PANDEMI COVID-19 SEBAGAI MOMENTUM KONSOLIDASI WISATA NOMADIK DI KAWASAN CANGGU, BALI - Bernada, Chelsea Chety; Roychansyah, M. Sani (Jurnal Perencanaan dan Pengembangan Kebijakan, 2023)
The Canggu area is one of the most popular nomadic tourist destinations in the world. This makes the development of the Canggu area increasingly important. With the COVID-19 pandemic, the nomadic style of tourism in the Canggu area has become adaptive tourism during the pandemic. This study aims to determine the stages of development of nomadic tourism in the Canggu area using a deductive qualitative method. The results of the study show that the Canggu area has undergone four stages: exploration, involvement, development, and consolidation. Observations show that currently Canggu Area tourism in the tourism area life cycle analysis is at stage 4, or the consolidation stage. COVID-19 has brought this area to a consolidation stage. The existence of the COVID-19 pandemic requires the concept of nomadic tourism to adapt and strengthen its quality. This has received a positive response as seen from a good reputation and structure in accommodating the needs of digital nomads that occurred during the pandemic in this region. so that the consolidation phase can strengthen the attractiveness of the Canggu Area as a nomadic tourism destination in the future.